Etho-Eco-Morphological Mismatches, an Overlooked Phenomenon in Ecology, Evolution and Evo-Devo That Supports ONCE (Organic Nonoptimal Constrained Evolution) and the Key Evolutionary Role of Organismal Behavior - Diogo, Rui (Frontiers in Ecology and Evolution, 2017)
Since ecomorphologists have started to use explicit and taxonomically-broad frameworks in studies on the relationships between form, behavior, ecology and phylogeny they have consistently reported - often against their expectations - 1) that phylogeny is a better predictor of anatomy than ecology is, and 2) many cases of etho-eco-morphological mismatches. It is puzzling that such mismatches occur frequently in an evolutionary process that often leads to macroevolutionary trends and in which organisms are said to be optimally/almost optimally 'designed' for the habitats they inhabit. Organic Nonoptimal Constrained Evolution (ONCE), a new perspective on biological evolution that is proposed here, addresses this apparent paradox, based on an extensive compilation of empirical data and broader evolutionary ideas, from Aristotle to current Evo-Devo. According to ONCE, by taking behavioral choices, and subsequently due to their behavioral persistence related to behavioral/ecological inheritance, organisms as diverse as bacteria, plants and animals help to construct their own niches and are thus the central, active players in their evolutionary history. The highly constrained character of organic evolution, including developmental constraints as well as the crucial role played by behavioral persistence, can dramatically limit the occurrence of new behavioral shifts and thus the responses to external (e.g., environmental) changes, often resulting in etho-eco-morphological mismatches and eventually in evolutionary dead-ends that may lead to extinction.